Current State of Surgical Management of Pancreatic Cancer - Hackert, Thilo (Molecular Diversity Preservation International (MDPI), 2011)
Pancreatic cancer is still associated with a poor prognosis and remains—as the fourth leading cause of cancer related mortality—a therapeutic challenge. Overall long-term survival is about 1–5%, and in only 10–20% of pancreatic cancer patients is potentially curative surgery possible, increasing five-year survival rates to approximately 20–25%. Pancreatic surgery is a technically challenging procedure and has significantly changed during the past decades with regard to technical aspects as well as perioperative care. Standardized resections can be carried out with low morbidity and mortality below 5% in high volume institutions. Furthermore, there is growing evidence that also more extended resections including multivisceral approaches, vessel reconstructions or surgery for tumor recurrence can be carried out safely with favorable outcomes. The impact of adjuvant treatment, especially chemotherapy, has increased dramatically within recent years, leading to significantly improved postoperative survival, making pancreatic cancer therapy an interdisciplinary approach to achieve best results.